2012
DOI: 10.2105/ajph.2012.300838
|View full text |Cite
|
Sign up to set email alerts
|

US Health Policy Related to Hookah Tobacco Smoking

Abstract: Background Although cigarette smoking is decreasing in the U.S., hookah tobacco smoking (HTS) is an emerging trend associated with substantial toxicant exposures. The purpose of this study was to assess how a representative sample of U.S. tobacco control policies may apply to HTS. Methods We examined municipal, county, and state legal texts that apply to the largest 100 cities in the U.S. We developed a summary policy variable that distinguishes cities without clean air legislation preventing cigarette or HT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 19 publications
1
68
1
Order By: Relevance
“…While regulation of tobacco products such as cigarettes is relatively comprehensive, the current regulation of HTS in the United States is confusing and inconsistent, possibly leading to the misperception that HTS is less harmful than cigarettes. Although the majority (73%) of the most populous U.S. cities have clean indoor air policies, it is unclear how these policies affect hookah bars and cafes, which are usually present in close proximity to university campuses (Primack, Hopkins, et al, 2012). Furthermore, hookah tobacco does not appear to be under the purview of the Family Smoking Prevention and Tobacco Control Act (U.S. Food and Drug Administration, 2012).…”
Section: Knowledge Of Htsmentioning
confidence: 99%
“…While regulation of tobacco products such as cigarettes is relatively comprehensive, the current regulation of HTS in the United States is confusing and inconsistent, possibly leading to the misperception that HTS is less harmful than cigarettes. Although the majority (73%) of the most populous U.S. cities have clean indoor air policies, it is unclear how these policies affect hookah bars and cafes, which are usually present in close proximity to university campuses (Primack, Hopkins, et al, 2012). Furthermore, hookah tobacco does not appear to be under the purview of the Family Smoking Prevention and Tobacco Control Act (U.S. Food and Drug Administration, 2012).…”
Section: Knowledge Of Htsmentioning
confidence: 99%
“…For businesses offering food and other sales items, it remains unclear if they will be less resistant to waterpipe regulation. A majority of New York City businesses offered food, and to our knowledge this provides the first direct evidence that many of these businesses may not actually be eligible for exemption from clean air regulations as a tobacco retail establishment as has been previous suggested (11). The average price of a standard waterpipe bowl was not prohibitive of daily use, especially if cost is shared within a group.…”
Section: Discussionmentioning
confidence: 71%
“…To avoid falling under existing CIAA regulations, US waterpipe business owners classify their business as retail tobacco shops, claiming waterpipe is their primary activity, with the sales of food and alcohol considered incidental. A 2012 study of the 100 largest US cities found 73 banned cigarette use within bars but 63 provided exemptions allowing waterpipe use (11).…”
Section: Introductionmentioning
confidence: 99%
“…The ambient air in hookah cafes has higher levels of particulate matter than restaurants that permit cigarette smoking and smoke-free restaurants (31). These risks to health notwithstanding, the vast majority of hookah venues are exempt from compliance with clean air standards (36,37).…”
Section: Physical Environmentmentioning
confidence: 99%
“…Prior reviews of the hookah smoking literature on college students have focused on epidemiology, specific subpopulations -particularly youths and college students (34), global health impact (35), health risks (8,28), and policy (36,37). This literature review examines hookah tobacco smoking within the context of the current mandate of the U.S. Food and Drug Administration (FDA) to regulate tobacco consumption.…”
Section: Introductionmentioning
confidence: 99%